2020
DOI: 10.1515/cclm-2019-0817
|View full text |Cite
|
Sign up to set email alerts
|

Development, optimization and validation of an absolute specific assay for active myeloperoxidase (MPO) and its application in a clinical context: role of MPO specific activity in coronary artery disease

Abstract: BackgroundMyeloperoxidase (MPO) is an enzyme with a recognized prognostic role in coronary artery disease (CAD), which is also emerging as a promising biomarker for cardiac risk stratification. However, the lack of a consensus method for its quantification has hindered its implementation in clinical practice. The aim of our work was to optimize an absolute sensitive assay for active MPO without external standards, to validate the method in the clinical context of CAD patients, and to estimate the enzyme specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Considerable studies have demonstrated the damaging effects of neutrophils on vascular endothelial cells in arterial dissection and ischemic brain tissues (20,(28)(29)(30)(31)(32). Due to the similar pathogenesis, we speculate that neutrophils play an important role in the occurrence and development of AIS caused by CCAD.…”
Section: Discussionmentioning
confidence: 74%
“…Considerable studies have demonstrated the damaging effects of neutrophils on vascular endothelial cells in arterial dissection and ischemic brain tissues (20,(28)(29)(30)(31)(32). Due to the similar pathogenesis, we speculate that neutrophils play an important role in the occurrence and development of AIS caused by CCAD.…”
Section: Discussionmentioning
confidence: 74%
“…More researches with diverse data characteristics and huge data sizes should be developed to validate the practicability of Lp-PLA2. Furthermore, in patients who are diagnosed with acute myocardial infarction, the MPO level is higher than patients with angina pectoris [49,50] or stable CAD [51]; meanwhile, there is a significant association between MPO concentration and angiographically detected coronary artery stenosis [52,53]. Rebeiz et al reported that elevation in plasma MPO could be used to identify coronary artery stenosis in 398 cases of negative chest pain with troponin patients, in which elevated quartiles of MPO concentration are closely associated with coronary artery stenosis, coronary thrombosis, and plaque ulcers [54].…”
Section: Lp-pla2mentioning
confidence: 99%
“…In particular, this modification makes the lipoprotein unable to promote cholesterol efflux and to contrast the oxidation of LDL [24]. The major culprit of this oxidative insult is myeloperoxidase (MPO) [166,173]. Indeed, HDLs isolated from patients affected by CVD contained high levels of 3-chlorotyrosine and 3-nitrotyrosine, products of the catalytic action of MPO [18,166].…”
Section: Type Of Study Main Findingsmentioning
confidence: 99%